1990
DOI: 10.1002/bdd.2510110703
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability and cardiovascular safety of dexatrim® (phenylpropanolamine hydrochloride) from a controlledrelease caplet

Abstract: The bioavailability and pharmacokinetics of phenylpropanolamine hydrochloride (PPA HCl) from a Dexatrim controlled-release (CR) caplet and solution was studied. Each subject (n = 12) received either a 75 mg PPA HCl CR caplet once daily or a 25 mg PPA HCl solution given three times a day. All subjects received the medication for 4 consecutive days. On Day 1, the mean +/- SEM, AUC, tmax, and Cmax values were 1651 +/- 127 ng x h ml-1, 4.5 +/- 0.26 h and 143 +/- 13.5 ng ml-1, respectively, for the CR caplet and 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
(2 reference statements)
0
7
0
Order By: Relevance
“…The pharmacokinetic parameters for pseudoephedrine and phenylpropanolamine administered in liquid formulations such as solution or syrup, have been established [3,4]. Findlay and colleagues [5] have examined the plasma pharmacokinetic parameters or pseudoephedrine following administration of multiple, therapeutic doses.…”
Section: Introductionmentioning
confidence: 99%
“…The pharmacokinetic parameters for pseudoephedrine and phenylpropanolamine administered in liquid formulations such as solution or syrup, have been established [3,4]. Findlay and colleagues [5] have examined the plasma pharmacokinetic parameters or pseudoephedrine following administration of multiple, therapeutic doses.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in absorption rate are common when a drug is coadministered with food, and it is well known that meals delay gastric emptying 21 . Previous reports have shown that LBM415 is completely absorbed from the gastrointestinal tract, suggesting that it has high permeability through the GI tract.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the peak plasma concentrations of phenylpropanolamine are not significantly different after the oral administration of equal doses of either immediate‐ or sustained‐release formulations (Hussain and others 1987, Lasagna 1988, Shargel and others 1990). After a single dose of an immediate‐release aqueous solution there is a rapid increase in the plasma concentration followed by a fairly rapid decline (Fig 1).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, sustained‐release preparations deliver the drug more slowly and the peak plasma concentration is reached more slowly (Lönnerholm and others 1984, Hussain and others 1987, Lasagna 1988, Shargel and others 1990). There is an initial release of drug that produces a plasma peak within the first few hours of the oral administration, and this is followed by a second slower absorption phase which continues over 16 hours and maintains the plasma concentration at a more constant level (Hussain and others 1987) (Fig 2).…”
Section: Discussionmentioning
confidence: 99%